Strategi Persaingan Pemasaran Indomaret dan Alfamart Menggunakan Game Theory (Studi Kasus Indomaret Alfamart Sayabulu, Kota Serang) - Indah Nuraeni; Iska Hayati; Nabila Saputri; Moh. Agus Awaludin; Bambang Hermawan (Indo Publishing, 2026)
This study aims to examine the marketing competition approach between adjacent Indomaret and Alfamart stores on Jalan Sayabulu, Serang City, using Game Theory. Data collection was conducted through direct observation. The marketing aspects analyzed include price, promotion, convenience, and product variety. Information obtained from observations was organized into payoff matrices and analyzed using the maximin and minimax methods. The findings reveal the presence of a saddle point indicating the success of the most efficient strategy. For Alfamart, the dominant strategy is the convenience aspect, while for Indomaret, the most effective strategy is related to price. This study indicates that Game Theory can be used as an efficient strategic analysis tool in modern retail competition in adjacent areas.